2009
DOI: 10.1177/0091552108330903
|View full text |Cite
|
Sign up to set email alerts
|

College Hopping

Abstract: Lateral transfer (between community colleges) is second only to upward transfer (to a 4-year institution) among community college students' most common patterns of transfer. Yet, upward transfer is the focus of innumerable studies, while lateral transfer has received very little empirical attention. This study explores the occurrence and frequency of lateral transfer in California and its consequences for the measurement of one particular outcome, namely, completion of a credential. The results indicate that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Moreover, students are more likely to transfer laterally early in their enrollment (Bahr 2012). Lateral transfer at community colleges also appears to be related to race/ethnicity and grant aid (Bahr 2009a), with African American or Black students more likely to laterally transfer than white students. Increased grant aid was associated with a decrease in likelihood of lateral transfer as well.…”
Section: Deconstructing Processes and Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, students are more likely to transfer laterally early in their enrollment (Bahr 2012). Lateral transfer at community colleges also appears to be related to race/ethnicity and grant aid (Bahr 2009a), with African American or Black students more likely to laterally transfer than white students. Increased grant aid was associated with a decrease in likelihood of lateral transfer as well.…”
Section: Deconstructing Processes and Outcomesmentioning
confidence: 99%
“…In education, research on student mobility has encompassed movement from one school to another (e.g., Rumberger andLarson 1998, Swanson andSchneider 1999;Bach et al 2000) residential mobility and it subsequent effects on changes in primary or secondary school (e.g., Kerbow 1996); transitions in grades or educational levels (e.g., Boudon 1974;Breen and Jonsson 2000); and course taking (e.g., Lucas 1999;Bahr 2009a), as a few examples. Even within a single field of study such as higher education student mobility is multifaceted.…”
Section: Student Mobilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, transfer pathways between two and fouryear institutions are complicated: only 24% of community college students who indicated a desire to transfer actually enroll in a four-year institution six years later (National Center for Education Statistics, 2011). In addition, research has found patterns of lateral transfers (Bahr, 2009), reverse transfers (Friedel & Wilson, 2015;Winter & Harris, 1999), and co-enrollment (Wang & Wickersham, 2014) between two and four-year institutions creating a student swirl among community colleges and universities. Given this complexity, some researchers have called for call for alternative classifications of higher education institutions not just by the type of credentials awarded but through a more multifaceted approach related to program and student characteristics (Skolnik, 2011).…”
Section: Coercive Isomorphismmentioning
confidence: 99%